The Polydectinae Dana, 1851, of the Philippines, with description of a new genus for Lybia hatagumoana Sakai, 1961 (Crustacea: Decapoda: Brachyura: Xanthidae) - Mendoza, Jose Christopher E.; Ng, Peter K. L. (Zootaxa, 2011)
The xanthid subfamily Polydectinae Dana, 1851, is recorded for the first time in the Philippines, being represented by four species: Polydectus cupulifer (Latreille, in Milbert, 1812), Lybia tessellata (Latreille, in Milbert, 1812), L. leptochelis (Zehntner, 1894), and L. hatagumoana Sakai, 1961. The taxonomy of L. hatagumoana is discussed at length, and a new genus, Tunebia gen. nov., established for it and the allied L. tutelina Tan & Ng, 1994, from New Caledonia. The new genus is diagnosed and compared with other polydectine genera.